"For Real Love": How Black Girls Benefit from a Politicized Ethic of Care. Issue 3 (July 2018) - Lane, Monique
This article examines the concept of a politicized ethic of care, a teaching philosophy that is commonly rooted in the pedagogies of exemplary Black female teachers. Data from a larger study of a girls' empowerment program at a public high school are used to argue in favor of this pedagogical tradition, which has been proven to facilitate the development of positive social identities and schooling behaviors among African American female students. The author challenges Western and gender-neutral approaches to caring for urban Black girls through an inductive analysis of curricula, in-class video footage, student artifacts, and interviews with former participants. Implications for teacher education research are presented.